PENGARUH PELATIHAN DAN KREATIVITAS TERHADAP PENGEMBANGAN USAHA PADA USAHA KECIL DAN MENENGAH DI PERKAMPUNGAN INDUSTRI KECIL PULOGADUNG JAKARTA TIMUR - Dedi Purwana E.S; Siti Juhaeriah; I Ketut R. Sudiarditha (Fakultas Ekonomi Universitas Negeri Jakarta, 2017)
This research aims to determine the impact of training and creativity on business development at the industrial village of small and medium enterprises, Pulogadung, East Jakarta. The research used survey method with correlational approach. Data were collected using questionnaire distributed to 33 business entities.Data were analyzed using the classic assumption test, multiple regression analysis and hypothesis test. The results revealed that: 1) training had a significant impact on business development; 2) creativity had a siginificant impact on business development; and 3) training and creativity had significant impact on business development simultaneously. Keywords: training, creativity, business development